Chapter 12: The politicization of immigration and welfare: The progressive's dilemma, the rise of far-right parties, and challenges for the left - Eger, Maureen A. (Edward Elgar Publishing, 2022)
According to the progressive's dilemma, diversity and solidarity are not easily combined, and this tension poses a political challenge for left-wing parties that embrace both. In this chapter, we measure the relationship among different configurations of immigration-welfare attitudes and support for political parties and candidates (far right, center-right, center-left, and far left). We focus on Sweden, Germany, and the United States - three major immigrant destinations that are also often regarded as the as the prototypical social democratic, conservative, and liberal welfare states. Using pooled cross-sectional data from the European Social Survey (ESS) and General Social Survey (GSS), we find that attitudes consistent with the progressive's dilemma have long existed. Results from multinomial logistic regression models reveal that anything but the most progressive attitudes make support for left-wing parties unlikely. Yet longitudinal trends suggest that the progressive's dilemma, while certainly a challenge for the political left, is not insurmountable.